Three new species of Collembola (Arthropoda: Hexapoda) from Brazil - Brito, Roniere A.; Lima, Estevam C. A.; Zeppelini, Douglas (Zootaxa, 2019)
Three new species of Collembola are described for Southeastern Brazil: Arrhopalites mendoncae sp. nov., Pararrhopalites queirozi sp. nov., and Coecobrya phoenix sp. nov. Although they were collected in caves and present characters such as absence of pigmentation, reduction or absence of eyes, and restriction to the local hypogean environment, none of them is troglobite. It is the first Coecobrya known from Brazil, the second species of the genus Arrhopalites with a trichobothrial complex angle superior to 160°, and the third species of the genus Pararrhopalites with three sensilla in the inter-antennal region. All species are named in honor of the Museu Nacional do Rio de Janeiro, and our colembologist colleagues, who recently had an entire collection destroyed by a fire of great proportions.